If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 26x + 72 = 36x Reorder the terms: 72 + 26x = 36x Solving 72 + 26x = 36x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36x' to each side of the equation. 72 + 26x + -36x = 36x + -36x Combine like terms: 26x + -36x = -10x 72 + -10x = 36x + -36x Combine like terms: 36x + -36x = 0 72 + -10x = 0 Add '-72' to each side of the equation. 72 + -72 + -10x = 0 + -72 Combine like terms: 72 + -72 = 0 0 + -10x = 0 + -72 -10x = 0 + -72 Combine like terms: 0 + -72 = -72 -10x = -72 Divide each side by '-10'. x = 7.2 Simplifying x = 7.2
| Qs=(-9)+3P | | Qs=(-9)+3P | | -4w+24=0 | | 18x+5x=-12x-1 | | (4v+6)(4v-6)=0 | | n+25=39 | | 4y+3y+5= | | 28x+66=33x | | -15x=-6x+3 | | 5q+11=2q+5 | | 5p-11=9p+7 | | 300=-222+a | | 6u-u= | | 0.80x+0.40(150)=0.40(150) | | 36+y=-66 | | 35=21y-7 | | 2x^2-9x+12=0 | | -14=-9z-16 | | 0=-5w+15 | | (x-6)=2x-12 | | 3+5x-6+2x=-4(x-3)+7 | | 36=-44+a | | .5(6x-8)=1.4(x-5)-.2 | | 36=-44+2 | | 0=6u-31 | | 0=6u-31 | | 11=-12+c | | 5h-12=4h+7 | | -8x+29=-7x | | 3=11+a | | .7(3x-5)+3.9x=14.5 | | 1-10x=91 |